ERP benefits capability framework: orchestration theory perspective - Badewi, Amgad; Shehab, Essam; Zeng, Jing; Mohamad, Mostafa (Emerald, 2017)
Purpose The purpose of this paper is to answer two research questions: what are the ERP resources and organizational complementary resources (OCRs) required to achieve each group of benefits? And on the basis of its resources, when should an organization invest more in ERP resources and/or OCRs so that the potential value of its ERP is realised? Design/methodology/approach Studying 12 organizations in different countries and validating the results with 8 consultants. Findings ERP benefits realization capability framework is developed; it shows that each group of benefits requires ERP resources (classified into features, attached technologies and information technology department competences) and OCRs (classified into practices, attitudes, culture, skills and organizational characteristics) and that leaping ahead to gain innovation benefits before being mature enough in realising a firm’s planning and automation capabilities could be a waste of time and effort. Research limitations/implications It is qualitative study. It needs to be backed by quantitative studies to test the results. Practical implications Although the “P” in ERP stands for planning, many academics and practitioners still believe that ERP applies to automation only. This research spotlights that the ability to invest in ERP can increase the innovation and planning capabilities of the organization only if it is extended and grown at the right time and if it is supported by OCRs. It is not cost effective to push an organization to achieve all the benefits at the same time; rather, it is clear that an organization would not be able to enjoy a higher level of benefits until it achieves a significant number of lower-level benefits. Thus, investing in higher-level benefit assets directly after an ERP implementation, when there are no organizational capabilities available to use these assets, could be inefficient. Moreover, it could be stressful to users when they see plenty of new ERP resources without the ability to use them. Although it could be of slight benefit to introduce, for example, business intelligence to employees in the “stabilizing period” (Badewi et al., 2013), from the financial perspective, it is a waste of money since the benefits would not be realised as expected. Therefore, orchestrating ERP assets with the development of organizational capabilities is important for achieving the greatest effectiveness and efficiency of the resources available to the organization. This research can be used as a benchmark for designing the various blueprints required to achieve different groups of benefits from ERP investments. Originality/value This research addresses two novel questions: RQ1: what are the ERP resources and OCRs required to achieve the different kinds of ERP benefits? RQ2: when, and on what basis, should an organization deploy more resources to leverage the ERP business value?
Keywords: ERP; Critical realism; Asset orchestration; Benefits management; Capability theories; ERP business value